Microbial functional diversity and carbon use feedback in soils as affected by heavy metals. (April 2019) - Xu, Yilu; Seshadri, Balaji; Bolan, Nanthi; Sarkar, Binoy; Ok, Yong Sik; Zhang, Wei; Rumpel, Cornelia; Sparks, Donald; Farrell, Mark; Hall, Tony; Dong, Zhaomin
Abstract: Soil microorganisms are an important indicator of soil fertility and health. However, our state of knowledge about soil microbial activities, community compositions and carbon use patterns under metal contaminations is still poor. This study aimed to evaluate the influences of heavy metals (Cd and Pb) on soil microorganisms by investigating the microbial community composition and carbon use preferences. Metal pollution was approached both singly and jointly with low (25 and 2500 mg kg −1 ) and high (50 and 5000 mg kg −1 ) concentrations of Cd and Pb, respectively, in an artificially contaminated soil. In a laboratory incubation experiment, bio-available and potentially bio-available metal concentrations, selected soil properties (pH, electrical conductivity, total organic carbon and total nitrogen), and microbial parameters (microbial activity as basal respiration, microbial biomass carbon (MBC) and microbial functional groups) were determined at two sampling occasions (7 and 49 days). Metal contamination had no effect on the selected soil properties, while it significantly inhibited both microbial activity and MBC formation. Contaminated soils had higher microbial quotient ( q CO2 ), suggesting there was higher energy demand with less microbially immobilized carbon as MBC. Notably, the efficiency of microbial carbon use was repressed as the metal concentration increased, yet no difference was observed between metal types ( p > 0.05). Based on the microbial phospholipid fatty acids (PLFA) analysis, total PLFAs decreased significantly under metal stress at the end of incubation. Heavy metals had a greater negative influence on the fungal population than bacteria with respective 5–35 and 8–32% fall in abundances. The contaminant-driven (metal concentrations and types) variation of soil PLFA biomarkers demonstrated that the heavy metals led to the alteration of soil microbial community compositions and their activities, which consequently had an adverse impact on soil microbial carbon immobilization. Highlights: Toxicities of soil Cd and Pb were determined both as single and combined effect. Readily and potentially bio-available soil metal concentrations varied over 49 days. Metal contamination impacted both soil microbial abundance and community structure. Soil fungal population was more sensitive to metal toxicity than bacteria. Metals reduced microbial q CO2 by 0.14–2.6 μg C mg −1 MBC h −1 compared to control.